Penguatan Kapasitas Pemasaran UMKM Rejosari melalui Pendekatan Branding Digital dan Desain Visual Canva - Aditiya Pratama Nugroho; Fatkhul Amin; Ratih Milati Ilham; Nabila Nur Fadilah; Sandy Ridwan Firmansah; Pradifaliani Nurhidayati (LPPM UNINUS, 2025)
This community service program aims to increase the capacity of micro, small, and medium enterprises (MSMEs) in Rejosari Village, Kangkung District, Kendal Regency, in utilizing digital marketing and graphic design using Canva. The main problem faced by the partners is the low ability of digital promotion and the use of social media as a marketing channel. This activity was carried out in a participatory and structured manner starting from needs assessment, socialization, training, mentoring, and evaluation. The training provided includes creating promotional content through visuals using the Canva application. The results of these activities show that the participants have significantly improved their design skills, and the basics of branding. This program has successfully encouraged MSMEs to actively increase the use of digital media to expand business market reach. The implication of achieving the objectives is that the combination of digital marketing and visual branding training is an effective strategy for community-based economic empowerment Keywords: MSMEs, digital marketing, Canva, community empowerment, branding